Systematic study on the role of Mn, Si, and Fe on the corrosion resistance of Ni-based superalloys exposed to air, gaseous sulfur oxides and salts - Rodenkirchen, Cynthia; Minns, Victoria; Encinas-Oropesa, Adriana; Nicholls, John R.; Hardy, Mark; Pedrazzini, Stella (Springer, 2026)
This work investigates the effect of alloying elements Mn, Si, and Fe on the corrosion resistance of polycrystalline Ni-based superalloys, at 700 C in air and 300 vpm SO2 under 5 lg cm2 h salt coating. Oxide scale morphology and composition was investigated using SEM–EDX and APT, revealing Mn–Fe-enriched Co3O4 particles in the upper outward growing scale as well as Si-Fe-enriched clusters in NiO. Along the NiO–Co3O4 phase boundary, a tight network of Fe-decorated dislocations relieving stress between the lattices was identified through APT. In the inward growing scale, Si enrichment was observed in the form of oxides and sulfides, while no Mn was detected.
Keywords: 40 Engineering; Materials; 4016 Materials engineering; 4017 Mechanical engineering